PENGARUH PENDEKATAN DISCOVERY LEARNING TERHADAP KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK KELAS X SMK NEGERI 1 KARANGANYAR DALAM OPERASI PERHITUNGAN MATEMATIKA - yugo attaufiq (Journal of Informatics and Vocational Education, 2020)
A This classroom action research was conducted in Class X Multimedia 4 with a total of 35 students. The objectives to be achieved in this study were to determine the process of implementing learning in increasing the activeness of class X students of SMK Negeri 1 Karanganyar in applying mathematical calculation operations. Increasing the activeness of implementing mathematical calculation operations for class X students of SMK Negeri 1 Karanganyar after participating in learning with the Discovery Learning model. Improved learning outcomes of class X SMK Negeri 1 Karanganyar after participating in learning with the Discovery Learning model. The technique used in this research is to make structured observations / observations in CAR-based learning activities. From the research that has been carried out, the results of the observations indicate that 22 out of 30 students (74%) seem to be active in the learning process. The scores of students resulting from the written test evaluation were only 7 students (24%) who still had not reached the KKM (minimum completeness criteria).